Investigations on the dynamic behaviour of an on-board rotor-AMB system with touchdown bearing contacts: modelling and experimentation. (October 2021) - Jarroux, Clément; Mahfoud, Jarir; Dufour, Régis; Legrand, Franck; Defoy, Benjamin; Alban, Thomas
Highlights: A multiphysics model comprising an on-board FE rotor, AMBs and TDBs is developed. Shock and harmonic tests on an on-board rotor-AMB kit permit validating the model. Rotor-TDB interactions are investigated using time response, orbit plots and STFT. Multi-harmonic response, peak flattening, particular orbits are investigated. Fleeting instabilities and short period of backward whirl are exhibited. Abstract: Active magnetic bearing (AMB) technology provides to rotating machinery, high operating speeds, direct couplings, almost frictionless support and a reduced footprint. In case of strong base excitations, the rotor may contact its touchdown bearings (TDBs), which are used as landing and safety bearings, while AMBs still operate. The paper presents, experimentally and numerically, this particular operating conditions where sliding friction-induced vibrations or AMB instabilities might be triggered. For this purpose, the developed finite-element model of the rotor-AMB-TDB system is experimentally validated using a lab-scale rotor test rig mounted on shaker. The validation is first conducted with no base excitation by analysing the mass unbalance responses and drop onto TDBs. In the presence of harmonic then impulse base excitations, the mass unbalance response are analysed in time and frequency domains. Considering harmonic tests, particular combinations of base motions and rotordynamics are observed depending on the frequency ratio between the base motion and the speed of rotation. TDB interactions produce rotor orbits flattening. The impulse tests highlight the friction effects and short periods of backward whirl are observed just after the contact. Despite some transient instabilities, the controller was always able to maintain the system stable by bringing damping. At each of these steps, the model reliability is assessed and predictions are close to the measured phenomena.